Don't let him in [compact disc, unabridged] - Jewell, Lisa (Simon & Schuster Audio, 2025)
Nick Radcliffe is a man of substance and good taste. He has a smile that could melt the coldest heart and a knack for putting others at ease. He's just what Nina Swann needed in her life after her husband's unexpected death. But to Nina's adult daughter, Ash, Nick seems too slick, too polished, too good to be true. Without telling her mother, Ash begins digging into Nick's past. What she finds is more than unsettling. Martha is a florist living in a neighboring town with her infant daughter and her devoted husband Alistair. But lately, Alistair has been traveling more and more frequently for work, disappearing for days at a time. When Martha questions him about his frequent absences, he always has a legitimate explanation, but Martha can't share the feeling that something isn't right. Nina, Martha, and Ash are on a collision course with a shocking truth that is far darker than anyone could have imagined.